Distinct cis-acting elements combinatorically mediate co-localization of mRNAs encoding for co-translational interactors in cytoplasmic clusters in S. cerevisiae - Shhade, Qamar; Estrada, Marianna E.; Hanna, Rawad; Makhzumy, Muhammad; Bar-Yosef, Hagit; Kramer, Günter; Bukau, Bernd; Shiber, Ayala (Journal of molecular biology, 2025)
Many newly synthesized proteins assemble co-translationally, providing a vital mechanism to prevent subunit misfolding in the crowded cytoplasm. Initial evidence indicates that the spatial organization of mRNAs aids this assembly, but it is unclear how these mRNAs are organized and how common this mechanism is. We used single-molecule Fluorescence in situ Hybridization in Saccharomyces cerevisiae to examine the spatial organization of mRNAs encoding subunits of various cytosolic complexes involved in critical cellular functions, such as fatty acid synthesis, glycolysis, translation and various amino acid biosynthesis. We found that mRNAs of the same protein complex often co-localize in specific cytoplasmic clusters. Additionally, we observed that the mRNAs encoding enzymes of biosynthetic pathways are organized in cytosolic clusters. Focusing on mRNAs encoding fatty acid synthase complex subunits, we discovered that non-coding cis elements significantly influence mRNA localization in an additive manner. Specifically, 5′ and 3′ UTRs, together with further upstream and downstream regions, facilitate co-localization. Inhibiting mRNA co-localization impaired growth when complex activity was essential, highlighting the importance of mRNA spatial organization for cellular survival. Transiently disrupting mRNA translation also affected clustering, indicating that both the nascent chains and mRNA sequence targeting cues are combinatorically contributing to spatial organization. Proteomics analysis demonstrates the impact of cis-elements on the abundance of the encoded subunits, as well as the entire pathway. In summary, we provide evidence that mRNA co-localization in cytoplasmic foci is coordinated by complementary mechanisms crucial for co-translational assembly, allowing efficient regulation of protein complex formation and entire pathways.
Gesehen am 02.03.2026